Effectiveness of Butterfly Hug Therapy in Reducing Anxiety Symptoms Among Older Adults: A Systematic Review - Nurpadilah, Demita; Albianto, Deranito Langlang Paresa; Firmansyah, Deni; Lismayanti, Lilis; Fauziah, Diny Nur; Firmansyah, Andan; Asmarani, Sri Utami (Genius Journal, 2025)
Introduction: Anxiety is a prevalent mental health concern among older adults, often triggered by chronic illness, cognitive decline, and social isolation. Left untreated, anxiety can significantly impair quality of life and exacerbate physical health issues. While pharmacological treatments exist, they pose potential side effects, especially for the elderly. Therefore, non-pharmacological approaches such as Butterfly Hug Therapy (BHT), a technique involving bilateral self-stimulation to promote emotional regulation, have gained attention as alternative interventions. Objective: This systematic review aims to evaluate the effectiveness of Butterfly Hug Therapy in reducing anxiety levels among older adults. Method: Following PRISMA 2020 guidelines, a literature search was conducted across PubMed, ProQuest, Garuda, and JSTOR from 2015 to 2024. Eligible studies involved elderly participants, reported measurable anxiety outcomes, and were published in English or Bahasa. Quality was assessed using the Critical Appraisal Skills Programme (CASP). Result: Out of 350 initial studies, three met the inclusion criteria. Sample sizes ranged from 2 to 60 participants, with therapy sessions lasting approximately 30 minutes over 1 to 2 weeks. Anxiety levels, measured using GAD-7 or GAI, consistently decreased after the intervention. Despite limitations such as small sample sizes and lack of rigorous controls, the findings support BHT as an effective strategy for anxiety reduction in the elderly. Conclusion: Butterfly Hug Therapy is a simple, non-invasive, and accessible intervention that shows potential for reducing anxiety in older adults. Further research through randomized controlled trials is recommended to confirm long-term benefits and establish standardized clinical guidelines.